The process approach in the financial management of insurance firms - Lech Gąsiorkiewicz (Foundations of Management, 2020)
The significance of insurance activity is constantly growing, generating new problems and posing new challenges. One of these challenges is meeting the growing requirements and expectations of customers. This requires the efficient management of insurance companies, which means the necessity to resort to modern management concepts, particularly the concept of process management and its related instruments. The article presents the results of research carried out at the Faculty of Management of the Warsaw University of Technology regarding process management in insurance companies. The distinctness of insurance activity and its financial management is discussed and its following aspects presented: the identification of insurance activity processes encompassing the management of basic and auxiliary processes; the model of the financial management process of insurance companies; the relationship between the financial management process and other processes implemented in insurance companies; financial situation assessment measures for insurance companies, and the financial management process.
Keywords: G22; 650; process management; process identification; financial management process; financial management process model; process relationships; process evaluation measures